Clinical and Radiological Outcomes of Total Knee Arthroplasty Performed with Midvastus and Medial Parapatellar Approaches in Obese Patients. (10th May 2021) - Guler, Olcay; Gümüşsuyu, Gürkan; Sofu, Hakan; Gökçen, Hüseyin Bahadır
Abstract : Background . The use of total knee arthroplasty (TKA) for primary osteoarthritis of the knee has remarkably increased recently. We aimed to compare the clinical and radiological outcomes of TKA in obese patients (>30 kg/m 2 ) operated with midvastus (MV) or medial parapatellar (MPP) approaches. Methods . This retrospective study was performed using data derived from 80 patients (70 women; 10 men) with an average age of 66.17 ± 5.42 (range: 54 to 77). Patients were allocated into 2 groups as for the type of approach conducted during TKA: group I ( n  = 41) underwent TKA by MV approach, while the MMP technique was used in group II ( n  = 39). Results . Demographic, clinical, and radiological parameters included age, side of involvement, sex, BMI, diameters of thigh and calf, length of incision, duration of operation, amount of bleeding and transfusion, duration of hospitalization and follow-up, complications, and range of motion, as well as Knee Society Score (KSS) and Knee Society Function Score (KSFS). Patients with a higher BMI (≥35 kg/m 2 ) experienced more profound bleeding and needed more transfusion of erythrocyte suspension. The range of motion was more favorable in groups with BMI <35 kg/m 2 . The functional outcomes as reflected in KSS and KSFS were much better in patients with BMI <35 kg/m 2 . Conclusions . Our data indicated that obesity can adversely influence the clinical and radiological outcomes after TKA performed by both MV and MPP approaches. A careful analysis of patient characteristics and selection of appropriate operative procedures is critical. Further randomized, controlled trials on larger series must be designed to elucidate the relationship between obesity and therapeutic outcomes after TKA with different approaches.